Penyelesaian Sengketa Pembiayaan Macet di PT. Bank mega syariah Melalui Pengadilan Agama (Studi Kasus Putusan No. 142/Pdt.G /2015/PA. Mdn) - Siti Salmiah (Fakultas Hukum universitas Islam Sumatera Utara, 2021)
Abstract Legal arrangements for settling bad debts at Islamic banks in accordance with the Sharia Banking Act can be through litigation and non-litigation channels. The settlement of litigation path is by submitting a lawsuit to the Religious Court, while the settlement through non-litigation channels is carried out through Basyarnas. The process of resolving bad debts based on sharia principles refers to banking legal provisions that are adjusted to the provisions of the DSN Fatwa and Compilation of Sharia Economic Law. The absolute competence of the Religious Courts in resolving financing is stalled on Islamic banks, which are still ambiquity. Because the absolute authority of the Religious Courts in resolving sharia banking disputes is then reduced after the issuance of the Sharia Banking Act which provides an opportunity for the General Court to resolve sharia banking disputes in accordance with the provisions of Article 52 paragraph (2) of the Sharia Banking Act.Keywords: Settlement, Financing, Religious Courts Abstrak Pengaturan hukum penyelesaian pembiayaan macet pada bank Syariah sesuai dengan Undang-Undang Perbankan Syariah dapat melalui jalur litigasi dan non litigasi. Penyelesaian jalur litigasi yaitu dengan mengajukan gugatan ke Pengadilan Agama, sedangkan penyelesaian melalui jalur non litigasi dilaksanakan melalui Basyarnas. Proses penyelesaian pembiayaan macet berdasarkan prinsip-prinsip syariah, mengacu pada ketentuan hukum perbankan yang disesuaikan dengan ketentuan Fatwa DSN dan Kompilasi Hukum Ekonomi Syariah. Kompetensi absolut pengadilan Agama dalam menyelesaikan pembiayaan macet pada bank syariah, masih bersifat ambiquitas. Karena kewenangan absolut Peradilan Agama dalam penyelesaian sengketa perbankan syariah kemudian direduksi setelah terbitnya Undang-Undang Perbankan Syariah yang memberikan peluang bagi Peradilan Umum untuk menyelesaikan sengketa perbankan syariah sesuai dengan ketentuan Pasal 52 ayat (2) Undang-Undang Perbankan Syariah. Kata Kunci: Penyelesaian, Pembiayaan, Pengadilan Agama.